Movimento intercultural curricular para políticas de formação de professores em contexto indígena: territórios, resistências e reconhecimento - Ruwer, Sheila Andreia (2022)
The present work presents a reflection on the formation of indigenous teachers, considering a policy movement for indigenous school education. The problem is: how is it possible to configure a curriculum guideline for training indigenous teachers, recognizing cultural plurality, in the context of public policies for training indigenous teachers in the state of Rio Grande do Sul. From the discussion of a theoretical artifact about interculturality and its imbrications with indigenous school education, the interrelationships between the training of indigenous teachers and teaching practices in the context of indigenous schools and their possible weaknesses and potential are discussed. Therefore, the theoretical-methodological assumptions are based on a research with a qualitative, autobiographical approach and a research-education dimension. Through the analysis of narrative interviews with indigenous teachers of the Kaingang and Guarani ethnicities, from the city of Santa Maria, having as central themes: interculturality, curricular production, indigenous school and teacher training, it was possible to establish some guidelines to guide educational policies for training initial and continuous training of indigenous teachers in the state of Rio Grande do Sul. The guidelines permeate three structuring axes that are interconnected: Territories, Resistances and Recognition, with the intention of reverberating in a training discourse in recognition of diversity based on citizen training and interculturality, being associated with projects and curricula for maintaining and strengthening the identity of indigenous peoples.